Business Strategy Development for Indonesian SMEs in Precision Manufacturing: A Case Study of PT. XYZ - Azkiya, Salma; Wandebori, Harimukti (Universitas Pamulang, 2025)
The rapid evolution of Industry 4.0, marked by advancements in automation, artificial intelligence (AI), and digital transformation, is reshaping global manufacturing competitiveness. Indonesia’s manufacturing sector, a key driver of economic growth, faces increasing pressure to adapt to these technological changes while addressing internal inefficiencies and market challenges. This study focuses on PT. XYZ, a precision manufacturing company operating in the SME sector, which has encountered declining revenue and operational bottlenecks despite its strong industry reputation. This research employs a comprehensive strategic analysis using internal (resource analysis, VRIO, value chain analysis) and external (PESTLE, Porter’s Five Forces, competitor analysis) frameworks to assess PT. XYZ’s market positioning and business challenges. The study further integrates SWOT and TOWS analysis to formulate strategic business solutions that leverage PT.XYZ’s core strengths, mitigate weaknesses, and capitalize on emerging opportunities in the precision engineering industry. Key findings indicate that PT. XYZ’s competitive advantage lies in its custom job-order specialization and strong client relationships, yet it faces limitations in financial resilience, workforce capabilities, and digital adoption. Based on the analysis, this study proposes an integrated business strategy emphasizing operational efficiency, financial resilience, market expansion, and digital transformation. The recommended implementation plan outlines short-term, medium-term, and long-term initiatives, including supply chain optimization, workforce upskilling, lean manufacturing adoption, and strategic partnerships. The findings contribute to understanding how SMEs in Indonesia’s manufacturing sector can navigate industry challenges, differentiate their offerings, and achieve sustainable growth in an increasingly competitive landscape.